Pengolahan Limbah Manure Padat Menjadi Pupuk Organik Menggunakan MOL di PT. P - Devy Apriliani; Teguh Taruna Utama (Yayasan Literasi Sains Indonesia, 2026)
Livestock waste is a type of waste produced from livestock activities. Problems caused by livestock waste include unpleasant odors that can interfere with breathing. This problem is caused by ammonia (NH3) and hydrogen sulfide (H2S) gas. This study aims to analyze the results of processing cow manure using MOL to be used as fertilizer in accordance with the Decree of the Minister of Agriculture of the Republic of Indonesia concerning Minimum Technical Requirements for Organic Fertilizers, Biofertilizers, and Soil Improvers in 2019. Cow manure has the potential to be used as compost. The content of nutrients such as Nitrogen (N), Fosfor (F), and Potassium (K) can increase soil fertility. The composting process can be carried out by adding materials containing microorganisms that decompose MOL. The fermentation process is carried out for 4 weeks. Changes that occur during the fermentation process include an increase in temperature and a dark brown color. Based on the test results, there was a decrease in the content of solid fertilizer. This is due to the fermentation time factor. The longer the fermentation time, the more nutrients are used for microorganism activity. This causes the availability of nutrients to decrease and be depleted. Experiments with better results can be carried out by reducing the length of the fermentation time. Further experiments can be carried out using solid manure waste as an additional nutrient in organic fertilizer made from vegetable juice.